Optimizing learning and motor performance in highly trained youth football players: the role of time interval between synchronous and asynchronous sessions in a blended training model - Haweni, A.; Tannoubi, A.; Gasmi, M.; Ursu, V. E.; Geanta, V. A. (Frontiers in Sports and Active Living, 2025)
Background/objectives: Effective motor performance in sport depends on the dynamic interaction between cognitive and physiological systems. However, it remains unclear how the temporal spacing between training sessions influences this interaction. This study examined the effects of the Time Interval Between Synchronous and Asynchronous Sessions (TIBSAS) on motor control and working memory in highly trained youth football players.